A Strategic Framework For Sustainable Tourism Development: Linking Culture, Destination Management, And Multi-Stakeholder Collaboration Case Study Of Baturaden, Indonesia - FX Setiyo Wibowo; I Gusti Ayu Oka Suryawardani; Marhanani Tri Astuti; Asep Parantika; Faidlal Rahman (Ministry of Tourism Republic of Indonesia, 2026)
The purpose of this study is to design an integrated model that links destination management and cultural management as a strategic framework for promoting sustainable tourism in the Baturaden tourism destination, Banyumas Regency, Indonesia. Based on the theory of Bentler and Ping Chou (1987), this research model uses 30 research indicators, then the number of samples used is 30 times 10, i.e 300 samples. The population of this study was multi-stakeholder, which included academics, businesses, communities, government, media, and visitors. The sampling system used was non-probability sampling, with a purposive sampling method. This study uses SEM analysis techniques employing SmartPLS to process data. Statistical analysis confirms that both cultural management and destination management exert significant positive effects on sustainable tourism (p < 0.05). Although destination management shows a stronger coefficient, cultural management remains essential for sustaining tourism development. The study introduces the ABCDE Model for Integrated Sustainable Tourism, which conceptualizes the dynamic relationship between Cultural Management, Destination Management, and Sustainable Tourism. This model is supported by five principal actors: A – Academician, contributing research and knowledge development; B – Business, providing investment and innovation; C – Community, preserving cultural identity and ensuring local participation; D – Destination Governance, ensuring policy coherence and strategic coordination; and E – Exposure Media, enhancing visibility and public engagement. The ABCDE Model thus provides a holistic approach to achieving sustainable tourism through synergistic, multi-stakeholder collaboration. To further strengthen and validate this model, additional empirical testing in diverse regional contexts is recommended. In policy terms, the ABCDE Model offers a concise strategic roadmap that local governments can adopt to integrate culture, governance, and sustainability into a single, measurable development framework.